Variety of Emotional Phenomena Classification - Tursunova Zarina Farkhodovna (International Journal on Integrated Education, 2023)
This article analyzes the concept of “emotion” and its types in the field of psychology. It divides several variants of negative and positive emotions of the person and its psychological effects.